Prophecy as trap - Landy, Francis (Studia theologica, 2015)
In Isaiah 6, the prophet is commissioned to speak so that people should not understand and thus be destroyed. The commission has parallels in other 8th century prophets, notably Amos and Hosea, for whom prophecy and history are a divine trap. I will proceed through a discussion of the ethical implications of the commission, using especially the ethical philosophy of Emmanuel Levinas, to a reading of particular texts: Isaiah 6, 29:1-14, and the Immanuel prophecy in 7:14-25. I will end with a consideration of reading and meaning. Criticism is a process of bafflement, of realising that one will never fully understand, that there are doors in the text one will never open.